Simultaneous Bilateral Spontaneous Pneumothorax in an Adult Patient With Pulmonary Langerhans Cell Histiocytosis: A Case Report - Vasileios Karamouzos MD; Christos Prokakis MD, PhD; Fotini Kosmopoulou MD; Evangelos Karanikolas; Christina Kalogeropoulou MD, PhD; Diamanto Aretha MD, PhD; Nikolaos Panagiotopoulos MD, PhD; Efstratios Koletsis MD, PhD; Dimitrios Velissaris MD, PhD (SAGE Publishing, 2018)
We report a case of a young female with known history of pulmonary Langerhans cell histiocytosis who was initially presented in the emergency department of a university hospital with respiratory distress. Clinical assessment and diagnostic workup revealed left hemithorax subcutaneous emphysema, bilateral pneumothorax, and atelectasis in both lower lung lobes. The patient was treated with bilateral staged thoracoscopic bullectomy and mechanical abrasion of the parietal pleura combined with chemical pleurodesis with talc. A new occurrence of right-sided pneumothorax was noticed 3 days after surgery, which was treated with chest tube insertion and chemical pleurodesis. The aforementioned surgical approach resulted in complete lung expansion and the patient's full recovery. A review of pulmonary Langerhans cell histiocytosis and treatment options in cases of pneumothorax due to lung histiocytosis is also presented in this report.